2019
DOI: 10.1021/acs.est.9b04065
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Enrichment Culture Responsible for the Complete Oxidative Biodegradation of 3-Amino-1,2,4-triazol-5-one (ATO), the Reduced Daughter Product of the Insensitive Munitions Compound 3-Nitro-1,2,4-triazol-5-one (NTO)

Abstract: 3-Nitro-1,2,4-triazol-5-one (NTO) is one of the main ingredients of many insensitive munitions, which are being used as replacements for conventional explosives. As its use becomes widespread, more research is needed to assess its environmental fate. Previous studies have shown that NTO is biologically reduced to 3-amino-1,2,4-triazol-5-one (ATO). However, the final degradation products of ATO are still unknown. We have studied the aerobic degradation of ATO by enrichment cultures derived from the soil. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…No significant NTO reduction in NC treatments indicated that NTO reduction was caused by the vetiver plants. Microbiological transformation of NTO to ATO to urea, CO2, and N2 has been reported earlier [2,10,11]. For this study, no transformation products of NTO were detected in the NTO-wastewater in NV treatments, indicating that NTO had been taken up by vetiver over time.…”
Section: Uptake Of Nto By Vetiver Grasssupporting
confidence: 66%
See 1 more Smart Citation
“…No significant NTO reduction in NC treatments indicated that NTO reduction was caused by the vetiver plants. Microbiological transformation of NTO to ATO to urea, CO2, and N2 has been reported earlier [2,10,11]. For this study, no transformation products of NTO were detected in the NTO-wastewater in NV treatments, indicating that NTO had been taken up by vetiver over time.…”
Section: Uptake Of Nto By Vetiver Grasssupporting
confidence: 66%
“…Under anaerobic conditions, NTO is biotransformed into ATO (3-amino-1,2,4-triazol-5-one), which requires further treatment based on regulatory standards. In a sequential anaerobic-aerobic biodegradation study, while NTO biotransformed into ATO under anaerobic conditions, ATO later mineralized under aerobic conditions [10,11]. Sorbents such as granular activated carbon (GAC) are ineffective, as NTO carries an electrostatic charge in aqueous solutions and sorbs very poorly to GAC [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Much research to date on the fate and treatment of NTO has focused on sorption 56–58 and biodegradation. 59–61 Because ATO can be readily mineralized to innocuous products such as CO 2 , NH 4 + , and N 2 , 62 reduction to ATO may be a first step to achieve complete NTO mineralization. Recent studies further showed that NTO can be abiotically reduced to ATO by geo-constituents including the hematite-Fe 2+ redox couple, 24 FeS minerals, 63 hydroquinones and humic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative processes such as biological and chemical oxidation have been shown to remove DNAN and NTO [17,18], but they could not remove NQ [18]. Several studies showed microbial degradation of NTO, NQ, and DNAN, suggesting biological treatment may be a viable option [12,13,16,[19][20][21][22]. NTO could be microbially transformed to 3-amino-1,2,4triazol-5-one (ATO) by mixed cultures under anaerobic conditions [16,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…NTO could be microbially transformed to 3-amino-1,2,4triazol-5-one (ATO) by mixed cultures under anaerobic conditions [16,20,21]. Madeira et al [22] reported that ATO was readily mineralized to CO 2 , N 2 , and NH 4…”
Section: Introductionmentioning
confidence: 99%